PERSEPSI ANGGOTA TERHADAP PERAN KELOMPOK TANI DALAM MENINGKATKAN KEMAMPUAN PENGUASAAN TEKNOLOGI BUDIDAYA BELIMBING - Diarsi Eka Yani (LPPM Universitas Terbuka, 2010)
This research aims are: (1) to identify factors related to the member perception on the role of farmer group; (2) to identify member perception on the role of farmer group related to competencies of farmer group member on the implementation of technology; and (3) to explain the role of agricultural extension workers to improve the ability of members on starfruit cultivation technology. Research uses a survey method, the population were farmer group member on Pasir Putih village, Sawangan district, Depok, with. number of samples were 40 people. The data were analyzed by the Spearman Rank test. Perceptions to the leadership group and group networking related significantly with perceptions of the role of members farmer group as study class. Experience farming management related significantly with perceptions of the farmer group member role as production unit farming management and cooperation vehicle. Farmer member group access by information related significantly with perception of the farmer group member as cooperation vehicle. The involvement of members in group activities related significantly with perceptions of the role of members farmer group as study class. The competencies of group member in skill technology related significantly to the role of group as study class and cooperation vehicle.